BIOTITE FROM RAPAKIVI - Velikoslavinsky D.A. (My University, 1994)
This paper deals with the chemical composition of biotites from rapakivi granites. For this purpose, 61 chemical analyses of biotites from composite anorthosite-rapakivi plutons in the Fennoscandian and Ukranian shields were used. Figurative points of the biotite composition were plotted on diagrams designed for biotites byFoster (1960),Winchell (1949) andVelikoslavinsky (1972). Consideration of the diagrams shows that a) the biotites from rapakivi granites have exotic composition not characteristic of other biotites from other igneous rocks, b) that they belong to the annite-siderophyllite series and c) that they crystallized at low pressures and high temperatures. Model crystallization temperatures range from 760 (early intrusive phases) down to less than 435 (late intrusive phase).